Characterization of a Novel Superoxide Dismutase from a Deep-sea Sea Cucumber (Psychoropotes verruciaudatus) - Yanan Li; Zongfu Chen; Peng Zhang; Feng Gao; Junfeng Wang; Li Lin; Haibin Zhang (MDPI AG, 2023)
At present, deep-sea enzymes are a research hotspot. In this study, a novel copper-zinc superoxide dismutase (CuZnSOD) was successfully cloned and characterized from a new species of sea cucumber Psychropotes verruciaudatus (PVCuZnSOD). The relative molecular weight of the PVCuZnSOD monomer is 15 kDa. The optimum temperature of PVCuZnSOD is 20 °C, and it maintains high activity in the range of 0-60 °C. It also has high thermal stability when incubated at 37 °C. PVCuZnSOD has a maximum activity of more than 50% in the pH range of 4-11 and a high activity at pH 11. In addition, PVCuZnSOD has strong tolerance to Ni2+, Mg2+, Ba2+, and Ca2+, and it can withstand chemical reagents, such as Tween20, TritonX-100, ethanol, glycerol, isopropanol, DMSO, urea, and GuHCl. PVCuZnSOD also shows great stability to gastrointestinal fluid compared with bovine SOD. These characteristics show that PVCuZnSOD has great application potential in medicine, food, and other products.